2019
DOI: 10.3390/ijms20215324
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Basic Research for Brain Arteriovenous Malformation

Abstract: Arteriovenous malformations (AVMs) are abnormal connections of vessels that shunt blood directly from arteries into veins. Rupture of brain AVMs (bAVMs) can cause life-threatening intracranial bleeding. Even though the majority of bAVM cases are sporadic without a family history, some cases are familial. Most of the familial cases of bAVMs are associated with a genetic disorder called hereditary hemorrhagic telangiectasia (HHT). The mechanism of bAVM formation is not fully understood. The most important advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 103 publications
(135 reference statements)
0
30
0
Order By: Relevance
“…About 5% of brain AVMs are linked to a genetic disorder, Hereditary Hemorrhagic Telangiectasia (HHT, Rendu-Osler-Weber Syndrome), which is an autosomal dominant vascular disease that affects approximately 1 in 5000 people worldwide [3]. The major clinical feature of HHT is hemorrhage from AVMs in multiple organs, including the brain.…”
Section: Tgf-signaling In Familial Brain Avmmentioning
confidence: 99%
See 4 more Smart Citations
“…About 5% of brain AVMs are linked to a genetic disorder, Hereditary Hemorrhagic Telangiectasia (HHT, Rendu-Osler-Weber Syndrome), which is an autosomal dominant vascular disease that affects approximately 1 in 5000 people worldwide [3]. The major clinical feature of HHT is hemorrhage from AVMs in multiple organs, including the brain.…”
Section: Tgf-signaling In Familial Brain Avmmentioning
confidence: 99%
“…Although clinical presentations are indistinguishable between HHT1 and HHT2, genotype-phenotype correlation studies have shown that HHT1 has a higher prevalence of AVMs in the brain and lungs, while HHT2 has a higher prevalence of AVMs in the liver and gastrointestinal tract. Brain AVMs are present in 10-16% of patients with HHT [3,37]. HHT1 patients have a significantly higher brain AVM prevalence (13%) compared with HHT2 patients (< 3%).…”
Section: Tgf-signaling In Familial Brain Avmmentioning
confidence: 99%
See 3 more Smart Citations